2021
DOI: 10.1155/2021/5013565
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Differentially Expressed Genes in the Dentate Gyrus and Anterior Cingulate Cortex in a Mouse Model of Depression

Abstract: Major depressive disorder (MDD) is a prevalent, chronic, and relapse-prone psychiatric disease. However, the intermediate molecules resulting from stress and neurological impairment in different brain regions are still unclear. To clarify the pathological changes in the dentate gyrus (DG) and anterior cingulate cortex (ACC) regions of the MDD brain, which are the most closely related to the disease, we investigated the published microarray profile dataset GSE84183 to identify unpredictable chronic mild stress-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 103 publications
0
11
0
Order By: Relevance
“…Anterior cerebrum The ACC is the first half of the cingulum gyrus, which is closely related to human cognitive execution, emotional processing, and other brain functions ( 34 ). When ACC is damaged, it will produce many clinical symptoms, including inattention, dysfunction of autonomic function regulation, emotional instability ( 35 , 36 ). Studies have found that the ACC is prone to damage in depression ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anterior cerebrum The ACC is the first half of the cingulum gyrus, which is closely related to human cognitive execution, emotional processing, and other brain functions ( 34 ). When ACC is damaged, it will produce many clinical symptoms, including inattention, dysfunction of autonomic function regulation, emotional instability ( 35 , 36 ). Studies have found that the ACC is prone to damage in depression ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of IDRs and LIPs in ZMIZ1 is consistent with its roles in the formation of multi-molecular complexes and transcriptional control, and potentially in the formation of super-enhancers. Recently, Zmiz1 has been identified as a super-enhancer associated gene, important for regulation of super-enhancer activity in response to estrogen during uterine development (58). Investigating the specific sequence determinants of these regions in the ZMIZ1 protein and their functional impact could offer valuable insights into the mechanisms governing Zmiz1-mediated signaling and regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Although these genes have no known role in corticogenesis, their known functions in other systems guided our hypotheses. HNRNPC, for instance, has a potential connection to post-synaptic genes in ASD and alternative splicing (Wei et al, 2021), whereas CXXC4 is known to regulate Wnt signalling and Tet2, potentially playing a vital role in cell survival and maturation (Byun et al, 2020). GNAL has been suggested to contribute to neurodevelopmental disorder aetiology through neurotransmission regulation (Myhre et al, 2021), while C1QTNF4 is involved in immune pathways and may be linked to the autoimmune responses observed in ASD (Sarver et al, 2021).…”
Section: Discussionmentioning
confidence: 99%